Unusual presentation of pediatric acute sphenoid sinusitis - Giordano, Davide; Perano, Daniele; Marchi, Sylvia; Raso, Maria Gabriella; Barbieri, Verter (Acta Biomedica Atenei Parmensis, 2014)
Background: Sphenoid sinus lesions are rare entities, occurring in 2 - 3% out of all paranasal sinus lesions. Isolated oculomotor nerve palsy due to acute sphenoid sinusitis is very rare, with only few cases reported in literature. Methods: Retrospective report about a case of isolated acute sphenoid sinusitis in a child with a left-sided third cranial nerve paralysis as the only sign at presentation. Results: Isolated oculomotor nerve palsy can be the initial sign of an isolated acute sphenoid sinusitis in children and it requires a high index of suspicion in order to avoid a delay in diagnosis. Conclusions: Magnetic resonance imaging should be promptly performed. Functional endoscopic sinus surgery represents the treatment of choice in order to restore sinus drainage and avoid further intracranial or ocular complications. The need of serial postoperative debridement under general anesthesia should be adequately scheduled and previously discussed with parents.